A protein-rich meal provides beneficial glycemic and hormonal responses as compared to meals enriched in carbohydrate, fat or fiber, in individuals with or without type-2 diabetes - Ekberg, Neda Rajamand; Catrina, Sergiu-Bogdan; Spégel, Peter (Frontiers in Nutrition, 2024)
Introduction Diet stands as a pivotal modifiable risk factor influencing weight gain and the onset of type-2 diabetes (T2D). This study delves into the variation in glucose and regulatory pancreatic hormone levels subsequent to the consumption of meals with differing macronutrient compositions. Methods The cohort comprised 20 individuals diagnosed with T2D and 21 without diabetes. Participants underwent a cross-over design, consuming four isocaloric meals (600 kcal) enriched in carbohydrate, fiber, fat and protein. Plasma glucose, insulin and glucagon levels were measured at -30, and -5 min, followed by subsequent measurements every 30 min for 240 min post meal intake. Quantification of alterations in the postprandial state was accomplished through the incremental area under the curve (iAUC) and the incremental peak height for the insulin:glucagon ratio (IGR) and plasma glucose levels. The meal demonstrating the lowest responses across these variables was deemed the optimal meal. Results Meals rich in protein and fat, and consequently low in carbohydrate, exhibited reduced incremental peak and iAUC for both glucose and the IGR in comparison to the other meals. While the protein-enriched meal neared optimal standards, it proved less efficient for individuals without T2D and possessing a low BMI, as well as in those with T2D and poor glycemic control. Conclusion Our findings endorse the adoption of protein-enriched, low-carbohydrate meals to curtail the meal-induced anabolic hormonal response while averting excessive fluctuations in glucose levels.